(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Psoriasis vulgaris is the commonest form of psoriasis. Ekakustha nearly resembles psoriasis as described in modern medicine. It is characterized by symptoms like - Asvedanam (loss of perspiration), Mahavastu (covered broad area of skin) Matsyashakalopama fish-like shiny lesions). These characteristic features are similar to psoriasis vulgaris. This study explores Ayurvedic management of psoriasis vulgaris. Methods: Lelitaka makshika yoga was prepared with reference in classical text. This is retrospective open label clinical case study. Lelitaka levigated with Amalaki svaras and Makshika bhasma levigated with Gaumutra, both combined with each other and make Lelitaka makshika yoga. Patient was kept on oral administration of Lelitaka makshika yoga vati for 8 weeks. Results: Sign and symptoms were assessed before treatment and after treatment. PASI and DLQI score was assessed before and after treatment. After 8 weeks of treatment scaling, skin thickness, sharply marginated, indurated, erythematous plaque was decrease on trunk, scalp, upper limb and lower limb. Significant improvement in psychological and social behaviour, which improve the quality of life of patients. Positive Auspitz’s and candle grease sign was negative after 8 weeks of treatment. Conclusion: Lelitaka -Makshika yoga vati is effective in the management of psoriasis vulgaris. After 8 weeks of observation, it appears Lelitaka -makshika yoga vati can be used to decrease disease progression.